A methodology to predict the aerodynamic characteristics of clean twisted wings at the condition of maximum lift - Ciro Otávio de Lacerda Badaró (2006)
The objective of this work is to present a methodology to predict the maximum lift of clean twisted wings. To this end, a methodology that couples aerodynamic input data from airfoils with a modified Weissinger method is implemented in a computational tool package. The model considers wings with break, sweep, and dihedral, whereas geometric and aerodynamic twists are properly considered by means of an interpolation technique. The analysis and validation procedure of the methodology is presented. A comparison with available data confirms both robustness and accuracy of the proposed numerical method.